Future Development Prospects of Green Bond Assessment - Yang, Yi; Zhao, Xiaowen (International Journal of Global Economics and Management, 2026)
Against the macro-background of China's efforts to promote a green and low-carbon economic and social transformation and implement the dual carbon goals, green finance has emerged as a core pathway to support low-carbon development. This paper reviews the current state of research on green bonds, analyzes the challenges in their value assessment work, and integrates domestic and international research findings with market practices. It explores optimized pathways for green bond valuation and provides an outlook on future development trends. The aim is to refine the theoretical framework for green bond assessment and promote the healthy and sustainable growth of China's green finance market.